The Association Between Grip Strength and Depression Among Adults Aged 60 Years and Older: A Large-Scaled Population-Based Study From the Longitudinal Aging Study in India - Wang, Jinbao; Zhou, Xianghong; Qiu, Shi; Deng, Linghui; Li, Jiakun; Yang, Lu; Wei, Qiang; Dong, Birong (Frontiers in Aging Neuroscience, 2022)
Background: The association between grip strength and depression in elderly individuals in low- and middle-income countries (LMICs) has rarely been studied. This study aims to explore the relevance of grip strength and depression in the elderly population using data from a national large-scale population. Methods: This study was conducted using data from seniors over 60 years old in wave 1 of the Longitudinal Aging Study in India (LASI). Grip strength is the maximum of three measurements by the dynamometer. Depression symptoms were assessed using 10 items on the Center for Epidemiologic Studies Depression Scale (CESD-10) with a 10-point boundary. Multivariate linear regression analysis, nonlinear analysis, subgroup analysis, interaction tests and sensitivity analysis were performed. Results: There were 27,343 participants in this study, including 19,861 participants with low grip strength and 7,482 participants with normal grip strength. The results revealed that grip strength and depression were negatively correlated in elderly individuals after adequate adjustment for confounding factors (odds ratio (OR)= 1.237, 95% confidence interval (CI) 1.172-1.305, p<0.00001). The results remained stable after adjusting for all confounding factors (OR=1.090, 95% CI 1.030-1.155, p= 0.00307). Regression analysis showed that physical activity (PA), comorbidities and cognition may have an impact on the correlation between grip strength and depression symptoms. Smooth curve fit suggested that grip strength and depressive symptoms were linearly related. The interaction test results of gender in the relationship between grip strength and depression were significant (p for interaction < 0.05). Conclusion: Grip strength and depression were negatively correlated in older Indians, and larger prospective studies are needed in the future to determine this association.